Effects of differing radiography certification requirements on income and certification status of dental assistants - Martin, Connor Jack (Kansas State University, 2022)
In recent decades, occupational licensing and certification has become a prevalent part of the U.S. economy and amongst the labor force. The dental assistant industry is a prime example of this labor theme as many are required to possess radiography certification to perform their most prominent task. Using data from the American Community Survey, the Current Populations Survey, and the Dental Assistant National Board, I modeled out the effects of differing certification regimes and the effects on income and certification status of dental assistants. Also, I use a state-level index that acts as a marker of the Scope-of-Practice dental assistants are permitted to accomplish in the workplace. States that do not impose a radiography certificate requirement sees certified dental assistants’ incomes rise by 9.5%. This contrasts with states that impose some certification requirement which see a null effect on certified dental assistant income relative to those not certified. Also, those without a high school diploma benefit the most of any education group from the certification as their incomes rise by 40.5%. Finally, through the state-level variable Prohibition Ratio, I found states expanding the SOP of dental assistants while keeping the number of prohibited tasks the same, will raise the incomes of dental assistants.
Keywords: Economics; Occupational licensing; Professional certification; Dental assistant; Protectionism